Diagnostic utility of ki67 and p53 immunostaining on solitary thyroid nodule - A cytohistological and radionuclide scintigraphic study - Monisha Choudhury; Smita Singh; Savita Agarwal (Wolters Kluwer Medknow Publications, 2011)
Background: For management of thyroid nodules, distinction between benign and malignant tumors is essential. Present study was undertaken to differentiate between benign and malignant lesions by using Ki-67 and p53 immunostaining and radionuclide perfusion scan. Materials and Methods: Study comprised of 25 prospective and 25 retrospective cases of solitary thyroid nodules. Fine needle aspiration was done on 25 prospective cases, which was correlated with histopathological diagnosis in 24 surgically excised cases. Immunostaining for p53 and Ki-67 was put on histopathological sections of 25 retrospective and 24 prospective cases. Radionuclide perfusion scan was performed and vascularity patterns were compared with their pathological nature to differentiate between benign and malignant nodule. Results: Cytohistological correlation was present in 80% of cases. On immunostaining, significant difference in mean value of Ki67 positivity was found between benign and malignant nodules (P < 0.05). On p53 immunostaining significant difference was observed in counts of benign and malignant lesions (P = 0.037). On radionuclide perfusion scan mean of difference between maximum and minimum perfusion activity between benign and malignant nodules was found to be statistically significant (P = 0.04), however there was no correlation between perfusion patterns and antigenic characteristics. Conclusions: P53 and Ki-67 immunostaining along with radionuclide perfusion scan appears to be useful tools to differentiate between benign and malignant lesions in solitary thyroid nodule; however, more studies are needed to confirm this observation.